Nutritional labeling, communication design, and relevance - Scott, Kate (Frontiers in Communication, 2023)
In this paper, I use relevance theory (Sperber and Wilson, 1995; Carston, 2002; Wilson and Sperber, 2012) to explain the relative effectiveness of three different nutrition labelling systems in communicating information and influencing consumer food choices. Facts Up Front (also known as Reference intake (RI) or Guideline Daily Amounts (GDA)), traffic light systems, and warning labels present nutritional information in different front of pack (FOP) formats. Research into the effectiveness of these systems shows that warning labels improve consumer’s ability to identify unhealthy products, compared with both Facts Up Front and traffic light systems. Warnings and traffic light systems perform equally well, however, when participants are asked to identify the most healthful product. I demonstrate how these findings can be explained in terms of the processing effort and inferential steps required from the consumer when accessing relevant contextual assumptions and deriving relevant implications in decision-making contexts. That is, I show how the success of the various labelling systems is linked to their relevance in the context of interpretation. This analysis illustrates the explanatory power of relevance theory in relation to visual communication and has implications for communication design and policy more generally.